The Impact of E-ticketing Implementation and Service Quality on Kai-Access Application User Satisfaction - Riris Amigo Simatupang; Gaby P.F Tampubolon; Pane, Idrus Hamonangan; Rinaldi, Muammar (Outline Journal of Management and Accounting, 2025)
The increase in digitalization within the transportation sector has driven PT Kereta Api Indonesia (PT KAI) to implement an e-ticketing system through the KAI Access application. However, there are still challenges related to service quality that may affect user satisfaction. This study aims to analyze the impact of e-ticketing implementation and service quality on user satisfaction with the KAI Access application. The research focuses on identifying factors that contribute to user experience and customer satisfaction. The study employs a quantitative approach using multiple linear regression analysis. Data were collected through questionnaires distributed to KAI Access users and analyzed using statistical software. The main variables examined include information quality, system quality, service quality, and customer satisfaction. More specifically, this research adopts a mixed-methods design with a sequential explanatory strategy. The initial quantitative phase involved 30 KAI Access users selected through purposive sampling. Multiple linear regression analysis was used to test the hypotheses regarding the influence of E-Ticketing (X1) and Service Quality (X2) on Customer Satisfaction (Y). The T-test results show that E-Ticketing (t = 2.565; p = 0.016) and Service Quality (t = 2.226; p = 0.035) each have a significant partial effect on Customer Satisfaction. Simultaneously (F-test), both variables also have a significant effect (F = 31.697; p = 0.001) with a contribution of 70.1% (Adjusted R Square). In the second phase, the qualitative analysis deepens these findings through in-depth interviews. Thematic analysis reveals that although users appreciate the ease of use, there are still notable complaints regarding system speed during peak hours and the need for additional features such as delay tracking. This study concludes that e-ticketing and service quality are strong predictors of customer satisfaction and recommends improving system performance to optimize the user experience.